1997
DOI: 10.1007/bf01979545
|View full text |Cite
|
Sign up to set email alerts
|

Comparative thermal analysis study of two biopolymers, starch and cellulose

Abstract: The degradation of cellulose and starch samples in air and nitrogen has been investigated by thermal analysis techniques. The techniques employed were differential thermal analysis, rising temperature and temperature jump thermogravimetry. Rate data were obtained from these experiments and Arrhenius parameters calculated from these values. This data was used to determine the mechanism by which the cellulose and starch samples degraded. The Arrhenius parameters were also calculated. The behavior of starch and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(33 citation statements)
references
References 19 publications
3
27
0
3
Order By: Relevance
“…After preoxidation at a temperature of 200°C under air atmosphere, some cracks can be seen on the surface of rice straw. Normally, hemicellulose components of lignocellulosic materials begin degrading over a temperature range of 150-350°C, and cellulose decomposes under an air atmosphere at a temperature above 250°C (Aggarwal et al, 1997;Kumer and Pratt, 1996). However, the study by Major (Major, 1958) indicated that cellulose started to be oxidized over a temperature range of 170-185°C, which is an apparent contradiction of the results obtained from other studies.…”
Section: Morphology Of Activated Carbonsmentioning
confidence: 82%
“…After preoxidation at a temperature of 200°C under air atmosphere, some cracks can be seen on the surface of rice straw. Normally, hemicellulose components of lignocellulosic materials begin degrading over a temperature range of 150-350°C, and cellulose decomposes under an air atmosphere at a temperature above 250°C (Aggarwal et al, 1997;Kumer and Pratt, 1996). However, the study by Major (Major, 1958) indicated that cellulose started to be oxidized over a temperature range of 170-185°C, which is an apparent contradiction of the results obtained from other studies.…”
Section: Morphology Of Activated Carbonsmentioning
confidence: 82%
“…E a is lower when thermal degradation occurs in air exposure compare to in nitrogen atmosphere. 22 This study was conducted in inert atmosphere with Nitrogen gas only in TGA chamber. Another factor is the polysaccharides film structural variation.…”
Section: Tga Trend and Activation Energy Calculationmentioning
confidence: 99%
“…~149 kJ/mol) [9] in SHS, and thermal decomposition reaction of starch and cellulose under nitrogen gas condition, 140~150 kJ/mol [11]. The value of Q 10 , the ratio of rate constant at (T+10)℃ to that at T℃ , for the carbonization in this study was about 1.7, and this value was considered to be in the range of thermochemical reaction.…”
Section: The Carbonization Rate Of Dried Ricementioning
confidence: 58%